2012
DOI: 10.1080/00028487.2012.728168
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Length Back‐Calculations from Otoliths and Scales Differ Systematically in Haddock

Abstract: Parallel macrostructure analysis of otoliths versus scales was conducted on Georges Bank Haddock Melanogrammus aeglefinus sampled in spring 2011 to test whether annuli widths of both structures yield comparable estimates of back‐calculated length at age. While generally similar in number, scale and otolith annuli were found to differ systematically in their relative widths, mainly because initial annuli are deposited closer to the origin in scales than in otoliths. Accounting for the delayed onset of scale ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 47 publications
2
5
0
Order By: Relevance
“…These results are consistent with those of other studies that have investigated the relationship between scale‐based and otolith‐based ages in numerous families of fish, including cyprinids (Vilizzi and Walker ; Simmons and Beckman ), a catostomid (Beckman and Huston ), a gadid (Baumann et al. ), a moronid (Secor et al. ), and salmonids (Zymonas and McMahon ; Schill et al.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results are consistent with those of other studies that have investigated the relationship between scale‐based and otolith‐based ages in numerous families of fish, including cyprinids (Vilizzi and Walker ; Simmons and Beckman ), a catostomid (Beckman and Huston ), a gadid (Baumann et al. ), a moronid (Secor et al. ), and salmonids (Zymonas and McMahon ; Schill et al.…”
Section: Discussionsupporting
confidence: 91%
“…Otoliths generally provide the most accurate and precise record of age (Baumann et al. ), although extraction and analysis of otoliths is more labor intensive than scale analysis and requires sacrifice of the study specimen. Verification of age by direct methods (Beamish and McFarlane ) and subsequent monitoring based on validated indirect estimates may be a cost‐effective and reliable approach for the long‐term management of imperiled species.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While otolith and scale growth were each proportional to somatic growth of Chinook Salmon, otolith growth was not proportional to scale growth. Baumann et al (2013) suggested that factors influencing otolith increment formation (e.g., metabolic rate) and scale circulus deposition (e.g., somatic growth) are different and that growth of these structures proceeds independently from each other.…”
Section: Structurementioning
confidence: 99%
“…Retrospective analysis is the reconstruction of fish size at an earlier age and is based on size relationships between an aging structure and fish length (Francis 1990). Back-calculation of fish length at a previous age is estimated by aging a hard structure and measuring its radius to a specific growth increment or annulus (Baumann et al 2013). Most fish species deposit regular increments on hard structures (Fisher and Pearcy 1990;Chittaro et al 2015), and increment-deposition frequency may be daily (i.e., otoliths; Bradford and Geen 1992;Bestgen and Bundy 1998) or related to growth rate (i.e., scales; Beamish et al 2004).…”
mentioning
confidence: 99%